Mobilities of Ti and Fe in disordered TiFe-BCC assessed from new experimental data. (September 2021) - Salmasi, Armin; Graham, Simon J.; Galbraith, Iain; Graves, Alexander D.; Jackson, Martin; Norgren, Susanne; Guan, Dikai; Larsson, Henrik; Höglund, Lars
Abstract: Pure titanium has an HCP structure and lacks mechanical properties for many industrial purposes. The BCC phase of Ti is required to make alloys with increased strength compared to pure Ti. Iron is the most potent element for stabilising the BCC phase. However, the addition of Fe to Ti causes segregation issues during solidification, which can be avoided by diffusion-driven solid-state alloying. To predict the diffusion kinetics, the interaction mobility parameters of Ti and Fe in the disordered BCC phase of Ti are necessary. In this work, these parameters are optimised based on new experimental data from Ti-Fe diffusion couples produced by the Field Assisted Sintering Technology (FAST). Diffusion couples were held at 1173K and 1273K for one hour. High-resolution Fe concentration profiles are obtained from Electron Probe Micro Analyser (EPMA). Ternary mobility interaction parameters are assessed based on binary endmembers with a DICTRA sub-module, and results are compared to earlier assessments of mobilities of the disordered BCC TiFe system.